Cation exchange capacity of bentonite in a saline environment. (January 2019) - Bohác, Peter; Delavernhe, Laure; Zervas, Erik; Königer, Franz; Schuhmann, Rainer; Emmerich, Katja
Abstract: Cation exchange capacity (CEC) is one of the basic characteristics of clays and clay minerals. Accessory minerals, such as carbonates, can influence the measured value of the CEC because of their dissolution. In the present study, the CEC of Ca-/Mg-bentonite Calcigel ® was studied by the Cu-trien method in the presence of NaCl at various concentrations (0–20 wt%). These conditions simulate the states of bentonite in geotechnical barriers during their hydration with saline solutions, e.g., in underground radioactive waste deposits. First, changes in the pH value, which were induced by Cu-trien and NaCl, were investigated, and the CECs of Calcigel/NaCl mixtures were measured and analyzed. Second, the influence of NaCl on the UV/Vis spectra of Cu-trien was tested. Third, the impacts of Cu-trien (3.33 × 10 −3  mol l −1 ) and NaCl on the solubilities of carbonate and dolomite were analyzed. The change in carbonate solubility, based on variations in the NaCl concentrations as well as the Cu-trien additions, has been identified as the main factor influencing the determination of the CEC of Ca-/Mg-bentonite Calcigel ® . With this knowledge of the solubilities of carbonates under controlled conditions and with the knowledge of bentonite mineral compositions, it is possible to correct the determined values of the cation exchange capacity. Highlights: Bentonites in geotechnical barriers e.g. in underground radioactive waste deposits are exposed to saline solutions during hydration. Salt admixture in bentonite after exposition influences CEC measurement. CEC of Ca-/Mg-bentonite Calcigel® was studied by Cu-trien method in the presence of the NaCl in various concentrations (0 – 20 wt%). The changes in accessory carbonates solubility, depending on the variations of electrolytes have been identified as the main factor influencing the CEC determination. "Blank correction" was successfully applied to improve the determined values of CEC.